2009
DOI: 10.1158/1078-0432.ccr-09-0048
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Multikinase Inhibitors Sorafenib and Sunitinib with Solute Carriers and ATP-Binding Cassette Transporters

Abstract: Purpose: To compare side-by-side the uptake of sorafenib and sunitinib in vitro by human uptake solute carriers of the SLC22A and SLCO families, the transport by and inhibition of efflux ATP-binding cassette (ABC) transporters, and the role of ABCB1 in the plasma pharmacokinetics and brain penetration of these agents. Experimental Design: Uptake of [ 3 H]sorafenib or [ 3 H]sunitinib was assessed in Xenopus laevis oocytes or mammalian cells transfected with cDNAs coding for human OATP1A2, OATP1B1, OATP1B3, OCT1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
115
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 49 publications
12
115
7
1
Order By: Relevance
“…The molecular mechanism underlying the sorafenib effect on ABCG2 efflux function is still under investigation. In addition to ABCG2, sorafenib blocks the function of other ABC transporters, including ABCB1, ABCC2, and ABCC4 (20,31). Hu and colleagues showed that sorafenib inhibits the ATPase activity of ABCC2 by directly interacting with this ABC transporter (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism underlying the sorafenib effect on ABCG2 efflux function is still under investigation. In addition to ABCG2, sorafenib blocks the function of other ABC transporters, including ABCB1, ABCC2, and ABCC4 (20,31). Hu and colleagues showed that sorafenib inhibits the ATPase activity of ABCC2 by directly interacting with this ABC transporter (31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ABCG2, sorafenib blocks the function of other ABC transporters, including ABCB1, ABCC2, and ABCC4 (20,31). Hu and colleagues showed that sorafenib inhibits the ATPase activity of ABCC2 by directly interacting with this ABC transporter (31). Carloni and colleagues reported that sorafenib decreases the expression level of ABCC2 in some breast cancer cell Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its bioavailability is influenced by the activity of the excretory transporters ABCB1 and ABCG2 in the small-intestinal mucosa (Hu et al 2009;Gnoth et al 2010). In addition, sorafenib is primarily metabolized by cytochrome P450 3A4 (CYP3A4) in the small-intestinal mucosa or the liver, and it is also subjected to glucuronidation mediated by uridine diphosphate glucuronosyl transferase (UGT) 1A9 (Lathia et al 2006;Peer et al 2012;Filppula et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In our hands there is a clear difference between 4 °C and 37 °C, indicating an active transport. Hu et al [44] already reported that both sunitinib and sorafenib do not appear to rely on active transport to enter the cell. These drugs are also not a highaffinity substrate for the ABC-family transporters, which is in agreement with the data reported by this study.…”
Section: Discussionmentioning
confidence: 99%
“…Only cimetidine and desipramine decreased the relative accumulation of sorafenib. It is possible that all three hOCT should be inhibited to see an effect in relative accumulation of sorafenib, although Hu et al [44] reported that sorafenib does not appear to rely on active transport to enter the cell. Nevertheless, none of the used hOCT inhibitors are specific.…”
Section: Discussionmentioning
confidence: 99%